Analisis Faktor yang Mempengaruhi Struktur Modal dengan Profitabilitas Sebagai Variabel Intervening pada Perusahaan Sektor Consumer Non-Cyclicals - Richard Febrianto Prayogo; Yohanes Frans Halawa; Nelly Sho (Universitas Methodist Indonesia, 2025)
This study aims to know and analyze the effect of liquidity, sales growth, company size, activity ratio and business risk on capital structure with profitability as an intervening variable. The population in this research amounted to 125 companies in the consumer non-cyclicals sector listed on the Indonesia Stock Exchange for the period 2020-2023. The sampling method used was purposive sampling and obtained 60 companies that became research samples. The data analysis method used is the Two-Stage Approach test using the SmartPLS version 3.2.9 application. The results showed that liquidity has a negative effect on capital structure and has no effect on profitability. While sales growth, company size, company activity and business risk have no effect on capital structure and profitability. Profitability is also unable to act as an intervening variable between liquidity, sales growth, firm size, activity ratio and business risk on capital structure.